2018
DOI: 10.1177/2325967118777842
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Screw Fixation Versus a Cortical Button and Self-tensioning Suture for the Latarjet Procedure

Abstract: Background:Metal screws are traditionally used to fix the coracoid process to the glenoid. Despite stable fixation, metal screws have been associated with hardware complications. Therefore, some studies have advocated for suture button fixation during the Latarjet procedure to reduce the complications associated with screw fixation.Purpose:To biomechanically evaluate the ultimate failure load of a cortical button and self-tensioning suture versus metal screws for coracoid graft fixation during the Latarjet pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 35 publications
4
66
0
2
Order By: Relevance
“…This method might help avoid impingement of the humeral head caused by malposition of the coracoid bony graft or its screws above the glenoid level with no reported neurological complications. Also, Provencher et al found a comparable biomechanical strength for coracoid bone block fixation between the screw and suture-button fixation techniques in Lataejet procedure 25 . The procedure remains technique demanding and, to our knowledge, few centers have reported clinical and radiologic outcomes for this surgical technique in China 26 .…”
Section: Introductionmentioning
confidence: 94%
“…This method might help avoid impingement of the humeral head caused by malposition of the coracoid bony graft or its screws above the glenoid level with no reported neurological complications. Also, Provencher et al found a comparable biomechanical strength for coracoid bone block fixation between the screw and suture-button fixation techniques in Lataejet procedure 25 . The procedure remains technique demanding and, to our knowledge, few centers have reported clinical and radiologic outcomes for this surgical technique in China 26 .…”
Section: Introductionmentioning
confidence: 94%
“…Recent clinical and biomechanical studies have confirmed that suture-button fixation devices provide mechanically strong constructs that are equivalent to the classically performed 2-screw technique. 11,18,37,38,52 After our successful clinical experience with the arthroscopic Latarjet procedure, we have developed an all-arthroscopic guided Eden-Hybbinette technique using the same guiding instrumentation and suture-button device (Bone-Link) for graft fixation. Herein, we describe this guided arthroscopic technique and report the clinical and radiological results in a series of 7 patients revised for a failed Latarjet.…”
mentioning
confidence: 99%
“…16,17,19,23,26 Suspensory fixation has been described previously in the literature through an open technique as an alternative to screw fixation of with a similar biomechanical strength. 16,31 Recently, Kalogrianitis et al 33 described an arthroscopic technique of iliac crest autograft bone augmentation with suspensory suture button fixation. However, the limitations of this graft include the lack of a chondral surface and significant donor site morbidity.…”
Section: E100mentioning
confidence: 99%
“…21,31,32 Fixation using suspensory cortical buttons has recently been described for the Bristow procedure and may be an attractive alternative to eliminate the complications associated with screw fixation. 16,31,33 Recently, the literature has reported suspensory fixation using iliac crest autograft; however, we discuss a technique for arthroscopic distal tibia allograft osteochondral fixation using suture button device. 33 The purpose of this technique is to describe the rationale and technical considerations behind the technique of osteochondral bone grafting of glenoid bone defects using a simple arthroscopic technique with suspensory fixation.…”
mentioning
confidence: 99%